Simulasi Realitas: Phubbing dan Hiperrealitas Pada Generasi Z di Kota Banda Aceh - Situmeang, Marini Kristina; Mentari, Mentari; Mawaddah, Mawaddah (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2025)
This study was conducted to examine the phenomena of phubbing and hyperreality among Generation Z in Banda Aceh, a region with a strong collectivist and religious cultural background. Phubbing, defined as the act of ignoring direct social interactions in favor of engaging with digital devices, was analyzed through the lens of Jean Baudrillards theory of hyperreality, which describes the collapse of boundaries between the real and the simulated in postmodern society. A qualitative phenomenological approach was employed to investigate the subjective experiences of individuals aged 1825. Data were collected through semi-structured in-depth interviews, limited field observations in various social settings (e.g., campuses, cafs, libraries, sports areas, and public spaces), and documentation (field notes and recorded interviews). The data were analyzed using phenomenological thematic analysis and primary data triangulation. The findings revealed that phubbing and hyperreality reflected a significant shift from authentic social reality to a digitally constructed one. Interpersonal relationships and identity formations were increasingly mediated by simulation, including curated social media content and the pursuit of digital validation. These changes were found to contribute to the erosion of face-to-face communication, social alienation, identity disorientation, and the normalization of antisocial behavior. Additionally, fluid and alternative identities were formed through digital self-representations rather than through traditional social interaction. Within Banda Acehs collectivist cultural context, the emergence of phubbing among Generation Z indicated a value conflict between traditional norms of direct engagement and the virtual connectivity offered by digital culture. These findings underscore the need for critical digital literacy, intergenerational dialogue, and the development of balanced digital engagement practices to support healthier social realities for young people in culturally rooted societies.